2018
DOI: 10.3389/fnins.2018.00156
|View full text |Cite|
|
Sign up to set email alerts
|

The Effects of Money on Fake Rating Behavior in E-Commerce: Electrophysiological Time Course Evidence From Consumers

Abstract: Online ratings impose significant effects on the behaviors of potential customers. Thus, online merchants try to adopt strategies that affect this rating behavior, and most of these strategies are connected to money, such as the strategies of returning cash coupons if a consumer gives a five-star rating (RI strategy, an acronym for “returning” and “if”) or returning cash coupons directly with no additional requirements (RN strategy, an acronym for “returning” and “no”). The current study explored whether a cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 45 publications
0
36
0
1
Order By: Relevance
“…First, previous research found that consumer preferences affected their rating choice and social interactions had an effect on the review generation process (Lee et al, 2015), providing empirical evidence enhancing our understanding of how social imitation and learning affect consumer rating generation. Second, recent studies found evidence of fake reviews in many contexts (Lappas et al, 2016;Wang et al, 2018). For example, in the context of hotel reviews, manipulating online reviews had a significant effect on changing product visibility (Lappas et al, 2016).…”
Section: Conceptual Framework Product Rating Generation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…First, previous research found that consumer preferences affected their rating choice and social interactions had an effect on the review generation process (Lee et al, 2015), providing empirical evidence enhancing our understanding of how social imitation and learning affect consumer rating generation. Second, recent studies found evidence of fake reviews in many contexts (Lappas et al, 2016;Wang et al, 2018). For example, in the context of hotel reviews, manipulating online reviews had a significant effect on changing product visibility (Lappas et al, 2016).…”
Section: Conceptual Framework Product Rating Generation Processmentioning
confidence: 99%
“…Social rewards (e.g., smiles and greeting cards) are important mediums that could have an effect on the product rating generation process. In addition, monetary rewards during the feedback stage can lead to false-positive rating behaviors (Wang et al, 2018). We speculated that monetary rewards during the priming stage might affect the product rating generation.…”
Section: Conceptual Framework Product Rating Generation Processmentioning
confidence: 99%
“…Concerning LPP in the late processing stage, the current study demonstrated both a significant main effect of game result and interaction between variables. An enhanced LPP within a time window of interest indicates a sustained involvement of cognitive resources and high emotional arousal on motivationally salient stimuli (Ma et al, 2018;Wang et al, 2018). Thus, the data from the present study suggested that defeat status (vs. draw) slowed the diminishment of involved attentional resources for displayed products; meanwhile, emotion arousal would be intense, implying a willingness to make purchase decisions on those products.…”
Section: Discussionmentioning
confidence: 51%
“…The ERP results provided more concise interpretations of information processing in compensatory consumption. At the preliminary stage, N1 showed similar patterns for all product images, suggesting a stable perceptual difficulty in perceptual behavior control (Wang et al, 2018). In other words, regardless of competition outcome and product category, this factor was homogeneous for those products in the participants' evaluation of purchasing disadvantage, including perceptual emergency and purchase conveniences.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation